Business incubation process and firm performance: An empirical review - Fidelis A. Ayatse; Nguwasen Kwahar; Akuraun S. Iyortsuun (Journal of Global Entrepreneurship Research, 2017)
Industrialization is central if any economy is to be successful and the policy attempts at industrialization involve creating systems and institutional arrangements that can help accelerate the process of industrialization. Business incubation is also a system and an institutional arrangement to help nations industrialize by developing the SME sector. This paper hopes to understand how the business incubation process influences firm performance. The methodology adopted is a comprehensive and extensive review of literature on the incubation phenomenon. The review found that firm performance is greatly enhanced when a firm avail itself to an incubation program. Revenue growth, employment or job creation, venture funding, networking and alliance building are the performance indices most impacted by the business incubation process. The paper recommends that prospective candidates for incubation should develop their market, management and financial plans to increase their chance of being selected as tenants. Also, firms are encouraged to access the value-addition services of incubation as this greatly increases their chances of firm survival, revenue growth, employment and job creation, financial resources and networking and alliance building. Furthermore, tenants should not overstay their tenancy in an incubation program as doing so reduces their chances of survival upon graduation.
Keywords: 650; Business incubation; Business incubation process; Business incubator and firm performance